Comparative Analysis of Intestinal Microflora Between Two Developmental Stages of Rimicaris kairei, a Hydrothermal Shrimp From the Central Indian Ridge - Qi, Li; Lian, Chun-Ang; Zhu, Fang-Chao; Shi, Mengke; He, Li-Sheng (Frontiers in Microbiology, 2022)
Though extreme physical and chemical characteristics, deep-sea hydrothermal vents still provide a place for fauna’s survival and reproduction. The symbiotic relationship of chemotrophic microorganisms had been investigated much more in the gill of Rimicaris exoculata, which are endemic in the hydrothermal vent of the Mid Atlantic Ridge. But there are only a few studies on intestinal symbiosis. Here we comparatively studied the intestinal fauna between juvenile and adult Rimicaris Kairei, which was another species in Rimicaris genus and originally discovered at the hydrothermal vent of Kairei and Edmond Fields in the Central Indian Ridge. Results showed that there were significant differences between juvenile and adult gut microbiota in species richness, diversity, and evenness. Especially for the species richness, the values of Chao1, Observed species, and ASV rarefaction curves indicated almost 4 times of species in adults compared to juveniles. For juveniles, the most abundant phylum was Deferribacterota with 80% occupation; while for adults, that was Campilobacterota with 49% account. Beta diversity showed that the intestinal communities of juveniles and adults were clearly classified into two clusters based on the evaluations of Bray-Curtis and weighted UniFrac distance matrices. Deferribacteraceae and Sulfourvoum were the main featured bacteria contributing to the difference. Moreover, Functional prediction for all of the intestinal microbiota presented that the pathways related to antibiotic synthesis, branched-chain amino acid biosynthesis, lipid metabolism, and cell motility appeared high abundance in juveniles. But for adults, the more abundance pathways were sulfur, carbohydrate, and biotin metabolisms. Taken together, these results indicated great differences in intestinal microbial composition and potential functions between juvenile and adult vent shrimps of Rimicaris Kairei, which may be related to their physiological needs at different stages of development.